Mixed-flow pump performance improvement based on circulation method - Chen, Jiaqi; Wang, Mengcheng; Bao, Yonghao; Chen, Xiao; Xia, Hepeng (Frontiers in Energy Research, 2023)
Mixed-flow pumps have been extensively employed in daily life, improving their energy characteristics contribute to the reduction of energy consumption worldwide. In this study, to overcome the decrease of optimization upper limit caused by using a single type of parameter as the design parameter, a typical mixed-flow pump was chosen for study, and its impeller was parameterized by five geometric and eight hydrodynamic parameters. With head and efficiency as the constraint and optimization objective respectively, 27 schemes were constructed by the Taguchi method. The influence of design factors to the objective and constraint was analyzed based on range and regression analysis. The optimization mechanism was elucidated using the entropy production method. The result reveals that the geometric and hydrodynamic parameters have a significantly impact on the mixed-flow pump’s energy characteristics. The optimized model head is 12.43m, which meets the constraints, while the efficiency increases by 3.2%–88.51%. Therefore, considering both geometric and hydrodynamic parameters in the mixed-flow pump optimization is workable and necessary. This paper can provide practical instructions on the optimal design of different turbomachines.